PERKEMBANGAN EKONOMI DALAM PEMIKIRAN PERSPEKTIF STUDI ISLAM - Malahayatie Malahayatie; Nurul Wahdini; Asra Asra; Nora Maulana (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research tries to examine the economic theories of previous Muslim thinkers which are considered very important for maintaining and developing the treasures of Islamic economics. The study was carried out using descriptive qualitative methods with data collection techniques using literature reviews or literature studies. The analysis of research data is studied by means of data reduction, data presentation and finally drawing conclusions. because the study is focused on library material by searching, reviewing and recording various literature in accordance with academic standard discussion points. This discussion is syntactically integrated, that is, it follows certain rules that can be logically connected to each other with the basic data observed. The research results show that in the Islamic perspective, Allah SWT is the supreme owner of everything on earth. Islam sees the economy as having to be run with a view towards property ownership. Human ownership is only relative and is limited to managing and using resources according to His instructions. In Islam, asset status is a direction or entrustment from Allah SWT to humans who are capable as His creatures. The idea of Islamic economic development forces and encourages humans to realize their true nature, namely the emergence of harmony between happiness in this world and the hereafter. Islamic development places a strong emphasis on moral and spiritual elements apart from outward manifestations which are not emphasized by conventional development. This research contributes to expanding public literacy regarding the theory and development of Islamic economics. It is hoped that the results of the study can become reference material and a source of reference in making decisions and making policies related to Islamic economic activities.